DAMPAK KETIDAKHARMONISAN KELUARGA DALAM PERKEMBANGAN KEHIDUPAN ANAK MENURUT HUKUM ISLAM DAN PERSPEKTIF SOSIOLOGIS (Studi Kasus di Desa Plososari Kecamatan Puri Kabupaten Mojokerto) - Dewi Chafshoh; Nur Hasan; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Families are the members consisting of father, mother and child is a strong unity if a good relationship is established between the father-mother, mother-son and father-daughter. Good relations is characterized by the harmony in the mutual relationships between individuals within the family. The interaction between each family member affects the state of happiness (harmony) or unhappy (disharmonies) on one or a family member. And when a family experiencing disharmony it will have an impact for all family members child. In this study will be presented How social development of children from families that are not harmonized and how the social impact on a child or family relationships are not harmonious in the village Plososari District of Puri Mojokerto. This research is a descriptive qualitative research with in-depth interviews on the subject which is then analyzed to obtain the results. These results indicate that the association of children who are victims of family disharmony largely towards negative as is often out at night, and become the bad boy in school, this is because the child was finding comfort in the world of relationships rather than on his family but also some children still grow up to be a positive person just as patiently, this is because the strong environment of the child is a positive environment. And the focus of the second study showed that children who are victims of family disharmony tend to close themselves off from the social environment so that it becomes being personally hard and do arbitrarily, but it will be different when the child is in an environment that is positive child would also be a positive person anyway, like being a private patient.Kata Kunci: Dampak Ketidakharmonisan Keluarga, Perkembangan kehidupan anak, Perspektif Sosiologis